A model of dimethylsulfide dynamics for the subtropical North Atlantic - Lefèvre, Mireille; Vezina, Alain; Levasseur, Maurice; Dacey John, W.H. (Deep Sea Research Part I: Oceanographic Research Papers, 2002)
International audience Dimethylsulfide (DMS) is a volatile sulfur compound produced by the marine biota. The flux of DMS to the atmosphere may act on climate via aerosol formation. It is therefore important to improve our understanding of the processes that regulate sea surface DMS concentrations for eventual inclusion into climate models. In order to simulate the dynamics of DMS concentrations in the mixed layer, a model of DMS production was developed and calibrated against a 1 year time-series of DMS and DMSP (dissolved and particulate) data collected in the Sargasso Sea at Hydrostation 'S'. The model reproduces the observed divergence between the seasonal cycles of particulate DMSP, the DMS precursor produced by algae, and DMS produced through the microbial loop from the cleavage of dissolved DMSP. DMSPp (particulate) reaches its maximum in the spring whereas DMSPd (dissolved) and DMS reach maximum concentrations in summer. Several parameters had to vary seasonally and with depth in order to reproduce the data, pointing out the importance of physiological and structural changes in the plankton food web. These parameters include the intracellular S(DMSp):N ratio, the C:Ch1 ratio and the sinking rates of phytoplankton and detritus. For the Sargasso Sea, variations in the solar zenithal angle, which co-vary with the seasonal variations in the depth of the mixed layer, proved to be a convenient signal to. drive the seasonal variation in the structure and dynamics of the plankton. Variations of the temperature and photosynthetically active radiation also help to reproduce the short-term variability of the annual S cycle. Results from a sensitivity analysis show that variations in DMSPp are dependent mostly on parameters controlling phytoplankton biomass, whereas DMS is dependent mostly on variables controlling phytoplankton productivity.